Unravelling gender‐specific factors that link obesity to albuminuria. (13th July 2020) - Landecho, Manuel F.; Alegría‐Murillo, Leire; López‐Fidalgo, Jesús; Colina, Inmaculada; Santesteban, Virginia; García‐Unciti, Marisol; Beloqui, Oscar; Frühbeck, Gema; Cuervo, Marta
Abstract: Background: Obesity is a major public health problem, which continues to be diagnosed and classified by BMI, excluding the most elemental concepts of the precision medicine approach. Obesity does not equally affect males and females, even with the same BMI. Microalbuminuria is a risk marker of cardiovascular disease closely related to obesity. The aim of this study was to evaluate the gender‐dependent differences in the development of early obesity‐related disease, focusing on pathologic microalbuminuria (PMA). Material and methods: We developed a single‐centre cross‐sectional study including 1068 consecutive adults from May 2016 to January 2018, divided into two groups: one including the first 787 patients attended, evaluated as a description population; the second group included 281 subjects analysed as an external validation population. Collected data included medical history, anthropometric measures, abdominal bioimpedance and routine laboratory tests. Results: First, we confirmed the lack of accuracy of classic obesity measures in predicting microalbuminuria. Second, we tested the utility of a tailored evaluation to predict PMA, with an area under the ROC curve of 0.78 for females and 0.82 for males. We also confirmed the different physiology of visceral adiposity for males when compared to females, in which small variations of fat mass entail major changes in the clinical repercussion. Third, we performed an external validation of our results, achieving a 77% accuracy rate. Conclusions: Our findings support that there is an individual threshold of fat amount necessary to develop obesity‐dependent PMA and that gender plays a major role in the interplay between PMA and adiposity.